Expression of FRS2 in atypical lipomatous tumor/well-differentiated liposarcoma and dedifferentiated liposarcoma: an immunohistochemical analysis of 182 cases with genetic data - Wenyi Jing; Ting Lan; Yan Qiu; Ran Peng; Yang Lu; Huijiao Chen; Min Chen; Xin He; Chen Chen; Hongying Zhang (BMC, 2021)
Abstract Background The fibroblast growth factor receptor substrate 2 (FRS2) gene is located close to MDM2 and CDK4 within the 12q13-15 chromosomal region. FRS2 gene was recently found to be consistently amplified in atypical lipomatous tumor (ALT)/well-differentiated liposarcoma (WDL) and dedifferentiated liposarcoma (DDL), suggesting the detection of FRS2 amplification could be a diagnostic tool for ALT/WDL/DDLs. However, the expression of FRS2 protein and diagnostic value of FRS2 immunohistochemistry (IHC) has not been evaluated in a large cohort of ALT/WDL/DDLs. Methods A SNOMED search of hospital surgical pathology files from January 2007 to July 2020 identified 182 ALT/WDL/DDLs with available materials. FRS2 fluorescence in situ hybridization (FISH) and IHC were performed on 182 ALT/WDL/DDLs and 64 control samples. The expression of FRS2 was also compared with that of classic immunomarkers (MDM2 and CDK4) of this tumor entity. Results This study included 91 ALT/WDLs and 91 DDLs. The FISH results showed 172 of 182 (94.5%) cases were FRS2-amplified, and 10 cases were FRS2-nonamplified. Immunostaining results showed 171 (94.0%) ALT/WDL/DDLs were positive for FRS2 and 11 cases (6.0%) were FRS2-immunonegative. In 172 FRS2-amplified cases, 166 (96.5%) were FRS2-immunopositive, and 6 (3.5%) were negative. Among 10 FRS2-nonamplified ALT/WDL/DDL cases, 5 cases were FRS2-immunonegative, and 5 tumors displayed 1+ staining for this marker. In 64 control cases, none of them exhibited FRS2 amplification. Forty-seven (73.5%) control cases were negative for FRS2 immunostaining, while 17 cases (26.5%) were FRS2-immunopositive. Fifteen of these false positive samples (15/17, 88.2%) showed 1+ positivity and only 2 cases (2/17, 11.8%) displayed 2+ positivity. In ALT/WDL/DDLs, the sensitivity of FRS2 immunostaining was slightly lower than MDM2 (FRS2 vs. MDM2: 94.0% vs 100.0%) and CDK4 (FRS2 vs. CDK4: 94.0% vs 97.0%). However, the specificity of FRS2 (73.5%) was slightly higher than that of MDM2 (67.8%) and CDK4 (64.4%). Conclusion This study indicated that FRS2 IHC had relatively good consistency with FRS2 FISH, suggesting that FRS2 immunostaining could be utilized as an additional screening tool for the diagnosis of ALT/WDL/DDL. It must be emphasized that MDM2/CDK4/FRS2 especially MDM2 FISH remains the gold standard and the most recommended method to diagnose this entity.